INNOVATIVE AIRSHIP DESIGN FOR REAL-TIME AIR QUALITY MONITORING USING IOT TECHNOLOGY - Prathik , Sudhir Jain; Sundaramahalingam , Athimoolam; Rajan S , Sudhagara; Solomon, Jenoris Muthiya; KN, Chethan; Keni, Laxmikant G (Journal of Applied Engineering Science, 2024)
The effect of poor air quality on human health has been linked to both short-term and long-term exposure to air pollutants. One of the most important steps in reducing emissions is accurate identification of these pollutants. This can be achieved by using Internet of Things equipped remotely operated airships that can survey large areas and gather pollution data. The ability of an airship to function at low altitudes for extended periods is the main design requirement of airships. This study describes a methodology for conceptualizing and building a helium-filled blimp for remote measurement of atmospheric pollutants (Carbon monoxide, Carbon dioxide, and Sulphur dioxide), temperature, and pressure. An onboard telemetry system measures the data while the airship is in flight and transmits them in real time to a ground-based station. The experiment showed that remotely operated airships are capable of gathering air data and their quality, enabling environmental scientists and regulatory agencies to better understand the behaviour of air pollutants and take steps to mitigate them.
Keywords: airships, helium, air quality, internet of things